Art‐on‐a‐Chip: Preserving Microfluidic Chips for Visualization and Permanent Display. Issue 34 (23rd July 2020) - Soffe, Rebecca; Mach, Albert J.; Onal, Sevgi; Nock, Volker; Lee, Luke P.; Nevill, J. Tanner
Abstract: "After a certain high level of technical skill is achieved, science and art tend to coalesce in aesthetics, plasticity, and form. The greatest scientists are always artists as well." said Albert Einstein. Currently, photographic images bridge the gap between microfluidic/lab‐on‐a‐chip devices and art. However, the microfluidic chip itself should be a form of art. Here, novel vibrant epoxy dyes are presented in combination with a simple process to fill and preserve microfluidic chips, to produce microfluidic art or art‐on‐a‐chip. In addition, this process can be used to produce epoxy dye patterned substrates that preserve the geometry of the microfluidic channels—height within 10% of the mold master. This simple approach for preserving microfluidic chips with vibrant, colorful, and long‐lasting epoxy dyes creates microfluidic chips that can easily be visualized and photographed repeatedly, for at least 11 years, and hence enabling researchers to showcase their microfluidic chips to potential graduate students, investors, and collaborators. Abstract : Art‐on‐a‐chip is a perfect combination of engineering, science, and art! A simple approach is presented here for preserving microfluidic chips with vibrant, colorful, and long lasting epoxy dyes that produce microfluidic chips that can easily be visualized and photographed repeatedly for at least 11 years, and hence enabling researchers to readily communicate their microfluidic research by using the microfluidic chip itself.